2006
DOI: 10.1038/sj.mp.4001873
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the shared biology of obesity and depression: the stress axis as the locus of gene–environment interactions

Abstract: Obesity and depression are serious public health problems and also constitute cardiovascular disease risk factors. Research organizations have called for efforts to explore the interrelationship between obesity and depression. A useful starting point is the fact that in both disorders there is dysregulation of stress systems. We review molecular and clinical evidence indicating that the mediators of the stress response are a key locus for geneenvironment interactions in the shared biology of depression and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(184 citation statements)
references
References 105 publications
3
174
1
6
Order By: Relevance
“…Fkbp5 is a strong candidate gene for stress-related metabolic disorders on the basis that it has already been identified as a candidate gene in depression, which shares common overlapping pathways with obesity (Bornstein et al 2006). Importantly, Fkbp5 knockout (51KO) mice are less affected by CSDS and show a reduced body weight compared with WT mice .…”
Section: Discussionmentioning
confidence: 99%
“…Fkbp5 is a strong candidate gene for stress-related metabolic disorders on the basis that it has already been identified as a candidate gene in depression, which shares common overlapping pathways with obesity (Bornstein et al 2006). Importantly, Fkbp5 knockout (51KO) mice are less affected by CSDS and show a reduced body weight compared with WT mice .…”
Section: Discussionmentioning
confidence: 99%
“…Increased food intake and reduced physical activity are characteristic of both conditions (94). Bidirectional causation is also plausible, with suggestions that obesity may be a determinant of later depression in children (97)(98)(99) and conversely hypothesized mechanisms for depression causing obesity (93,95,(98)(99)(100). Indeed, it has more recently been suggested that these two comorbid conditions may mutually reinforce a progressive downward spiral in each other (101) and that additional insight into their longitudinal interaction may be important for intervention strategies (102).…”
Section: Psychosocial Vulnerabilitiesmentioning
confidence: 99%
“…This comorbidity may be due to common genetic and environmental etiologies (93)(94)(95)(96) or common pathways via dysregulation of the hypothalamic-pituitary-adrenal system (93,95,96). Increased food intake and reduced physical activity are characteristic of both conditions (94).…”
Section: Psychosocial Vulnerabilitiesmentioning
confidence: 99%
“…A global health approach is needed to tackle inequalities in health between the industrialized and developing world. 4,5 A global health strategy has to take into account political, epidemiological, environmental, infrastructural and genetic aspects. The aim is to accomplish the greatest benefit for the most people over the longest period of time and that our significant, but finite, resources are used most effectively.…”
Section: Global Healthmentioning
confidence: 99%